2016
DOI: 10.1111/jcmm.12796
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer efficacy of a nitric oxide‐modified derivative of bifendate against multidrug‐resistant cancer cells

Abstract: The development of multidrug resistance (MDR) not only actively transports a wide range of cytotoxic drugs across drug transporters but is also a complex interaction between a number of important cellular signalling pathways. Nitric oxide donors appear to be a new class of anticancer therapeutics for satisfying all the above conditions. Previously, we reported furoxan‐based nitric oxide‐releasing compounds that exhibited selective antitumour activity in vitro and in vivo. Herein, we demonstrate that bifendate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Consistent with above research, we also found high iNOS expression plays a positive role in the prognosis of patients with HCC and suggesting that iNOS can be used as a specific target for HCC treatment. Aberrant protein nitration by nitric oxide, produced by dimerization of iNOS, plays a key role in cancer recurrence and development (48).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with above research, we also found high iNOS expression plays a positive role in the prognosis of patients with HCC and suggesting that iNOS can be used as a specific target for HCC treatment. Aberrant protein nitration by nitric oxide, produced by dimerization of iNOS, plays a key role in cancer recurrence and development (48).…”
Section: Discussionmentioning
confidence: 99%
“…Low concentration of NO can promote invasion and metastases in different tumor models, and high concentration of NO can inhibit tumor growth and metastases. 32 , 33 NO alone shows a high IC 50 concerning its cytostatic efficacy, while the reported anticancer candidates with NO-releasing residue have much lower IC 50 (from hundreds nanomoles to several micromoles). It has been reported by Heigold et al that NO induced apoptosis selectively in NOX-expressing transformed cells through formation of peroxynitrite in early stages of carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, high levels of NO (above 400 nM [33]) produced from NO donors can induce apoptosis, inhibit metastasis of tumor cells, and sensitize tumor cells to radiation, immunotherapy, and chemotherapy. Some synthesized NO-releasing compounds have already shown antitumor activity against human carcinoma cells in vitro and in vivo [21][22][23][24][25][26][27][28][29][30][31][32]. Due to the highly reactive nature of NO, it is difficult to predict its biological effects on a given system from single doses even if provided by the longer action of inducible nitric oxide synthase (iNOS).…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide (NO), one of the simplest, odorless, colorless, highly reactive, and biological molecules in nature, is a free radical and a key mediator involved in diverse physiological and pathological processes [16][17][18][19][20]. NO-donating compounds have recently come into focus for the treatment of tumors because NO plays a central role in cell regulatory pathways and is a key signaling molecule involved in the death and apoptosis of tumor cells [21][22][23][24][25][26][27][28][29][30][31][32]. Generally, high levels of NO (above 400 nM [33]) produced from NO donors can induce apoptosis, inhibit metastasis of tumor cells, and sensitize tumor cells to radiation, immunotherapy, and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%